Immunuhistochemical features of the ovaries' structure in case of fetuses with a gestational term of 21-28 weeks from mother, whose pregnancy was complicated by chronic infections of lower genital tracts - V. O. Poliyasnyi; L. S. Kupriianova (Kazimierz Wielki University, 2021)
The following article presents results of the complex research on postulation of immunohistochemical features of the ovaries' structure in case of fetuses with a gestational term of 21-28 weeks from mothers with HILGT comparing to ones in case of fetuses from mothers with a physiological pregnancy. The materials of the research are: 25 fetuses from mothers with HILGT as well as 25 fetuses from mothers with physiological pregnancy. All fetuses had died antenatally and inranatally, as a result of violation of uteroplacental and umbilical-uterine circulation. Research methods: macroscopic, organometric, histological, immunohistochemical, morphometric, statistical. The organometric method revealed a clear decrease of main indexes of the fetuses' ovaries from mothers with a complicated pregnancy comparing to ones in case of organs of fetuses from healthy mothers. Morphometric method revealed a clear decrease of a relative volume of cortical substance as well as a clear increase of a relative volume of brain substance in the gonads of fetuses from the main group; as well as it showed a clear decrease of an index of follicular tissue' relative volume, likewise a clear increase of an index of interstitial component relative volume. The staining by picrofuxin by van Gieson method revealed a massive growth of the connective tissue in all strucutral components of organs of fetuses from mothers with HILGT relatively to gonads of fetuses from healthy mothers. Using of MCAT to main types of collagens allowed to reveal a violation of maturation of main types of collagens in the structure of connective tissue of fetal gonads in the main group. In the follicular component of the fetuses' ovaries in the main group are appearing mature, cystic-artretic and growing forms of follicles. Immunohistochemical method revealed an increased number of an apoptotically altered eggs in the ovaries of fetuses from mothers with HILGT comparing to one in organs of fetuses from mothers with physiological pregnancy.  The peroxidase method revealed an increased endotheline-producing activity of the vascular component as arterial, like a venous type; likewise a clear decrease of the hormone-producing activity in the ovaries of fetuses from mothers with HILGT comparing to such indexes in fetal organs of fetuses from mothers with physiological pregnancy. The complex of changes in the ovaries of fetuses with a 21-28 weeks of gestational term, which was described, was formed under the influence of the chronic hypoxia, prolonged antigenic stimulation as well as hormonal violations in the mother-placenta-fetus system, which is a leading link of the infectious pathology' pathogenesis. The aforementioned complex of the structural and functional changes in the ovaries of fetuses from mothers with HILGT in a gestational term of 21-28 weeks indicates violations in implementation and formation of the fetal gonads, as well as it could further lead to disorders of the germinal function in the female organism.